1994
DOI: 10.1021/tx00042a022
|View full text |Cite
|
Sign up to set email alerts
|

An Aziridinium Ion Intermediate in the Nitrosation of a Hexetidine Model

Abstract: The nitrosation chemistry of 1,3,5-trimethyl-5-aminohexahydropyrimidine (2) has been investigated as a model for the behavior of the antimicrobial agent hexetidine (1) under similar conditions. The reaction of 2 with sodium nitrite in glacial acetic acid gives 4-methyl-4-[(methylnitrosamino)methyl]-3-nitroso-1,3-oxazolidine (4) as the major nitrosamine. This compound arises from a molecular rearrangement which proceeds through the diazotization of the primary amino group followed by intramolecular displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The nitrosation of hexetidine and related model compounds was undertaken to test the hypothesis that geminal diamines would be susceptible to rapid nitrosation with ensuing generation of nitrosamines. This publication and the accompanying paper (4), which reports the results of a related model study, clearly support this hypothesis. In a preliminary account Loeppky et al reported that the nitrosation of hexetidine resulted in the rapid pro-duction of at least eight different nitrosamines (3).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…The nitrosation of hexetidine and related model compounds was undertaken to test the hypothesis that geminal diamines would be susceptible to rapid nitrosation with ensuing generation of nitrosamines. This publication and the accompanying paper (4), which reports the results of a related model study, clearly support this hypothesis. In a preliminary account Loeppky et al reported that the nitrosation of hexetidine resulted in the rapid pro-duction of at least eight different nitrosamines (3).…”
Section: Introductionsupporting
confidence: 62%
“…It is remarkable that there does not appear to be significant nitrosation and deamination of the primary amine in hexetidine. This pathway was found to be the major pathway for the nitrosation of a hexetidine model compound where the 2-ethylhexyl groups were replaced with methyl groups (4). While the reasons for the differences in reactivity are still under active investigation, a simple rationalization for the reactivity is related to the probable differences in basicity of the primary and tertiary amines in hexetidine, as discussed above.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The mechanism and kinetics of nitrosative dealkylation of trialkyl tertiary amines have been investigated. , A key marker of this mechanistic pathway, shown as path A ( 1 → 4 → 8 → 2 ) in Scheme , is the formation of 0.5 mol of N 2 O for every mole of nitrosamine formed. We have identified other structural features of tertiary amines which render them highly reactive toward nitrosative dealkylation and demonstrated that they occur by different mechanisms than that shown in path A of Scheme , but none of these would appear to be applicable to the reactions of N,N -dialkyl anilines. Our preliminary investigations of the nitrosation of 1 (X = CO 2 Et) showed that the relative yields of nitrosamine and nitro compound vary significantly with relatively minor changes in reaction conditions. These data suggested the operation of facile mechanistic switching and led us to consider a possible role for radical cation intermediates in the nitrosation chemistry of these aromatic amines.…”
Section: Introductionmentioning
confidence: 98%